1984
DOI: 10.1007/bf00022751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brassica genotypes for resistance to shatter. I. Development of a laboratory test

Abstract: INDEX WORDSBrassica spp ., shatter-resistance, siliqua strength, field shatter . SUMMARY A new test procedure for measuring shatter-resistance of siliquae of Brassica s pp . i s described . A siliqua with its proximal end clamped is loaded as a cantilever in a testing machine . The maximum bending moment, the corresponding stiffness and the energy to cause the siliqua to rupture were taken as measures of the resistance of the siliqua to shatter . Studies showed that ranking of accessions based on either bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 3 publications
2
37
0
2
Order By: Relevance
“…Peng-Fei et al (2011) evaluated 220 lines of B. napus for shatter resistance using 'ripping' method (Tan et al 2007) and showed that ripping force ranged from 1.46N to 4.23N. The levels of pod strength reported in this study appear to be in general agreement with studies in Australia (Kadkol et al, 1984;Raman et al, 2011) indicating limited genetic variation in B. napus. Raman et al (2011) evaluated 181 accessions of Brassica napus, one B. rapa, three B. juncea and two accessions of B. carinata, using a pendulum test (Kadkol, 2009) in two separate experiments.…”
Section: Genetic Variation For Shatter Resistancesupporting
confidence: 81%
See 4 more Smart Citations
“…Peng-Fei et al (2011) evaluated 220 lines of B. napus for shatter resistance using 'ripping' method (Tan et al 2007) and showed that ripping force ranged from 1.46N to 4.23N. The levels of pod strength reported in this study appear to be in general agreement with studies in Australia (Kadkol et al, 1984;Raman et al, 2011) indicating limited genetic variation in B. napus. Raman et al (2011) evaluated 181 accessions of Brassica napus, one B. rapa, three B. juncea and two accessions of B. carinata, using a pendulum test (Kadkol, 2009) in two separate experiments.…”
Section: Genetic Variation For Shatter Resistancesupporting
confidence: 81%
“…These tests are somewhat subjective and are often not necessarily comparable due to the difference in maturity and moisture status of siliquae or differences in environmental conditions (Morgan et al, 1998 Table 2. Early tests used to identify shatter resistance in Brassica species Kadkol et al (1984) suggested that the methodology used to test siliqua shatter resistance should simulate shattering as it occurs in the field and during harvesting. They further suggested that it would be most appropriate to test the siliqua as a cantilever because most external forces acting on the siliqua would load it at the distal end whilst it is attached to the plant at the proximal end.…”
Section: Methods For Screening Germplasm For Shatter Resistancementioning
confidence: 99%
See 3 more Smart Citations